THE DIRECT AND INDIRECT EFFECT TAX PAYER UNDERSTANDING ON TAX PAYER COMPLIANCE BY TAX COMPLIANCE COST - Juliardi, Dodik; Sudarto, Triadi Agung (International Journal of Business, Law, and Education, 2023)
The purpose of this research is to test Taxpayer understanding and Tax Compliance Costs regarding Taxpayer Compliance. Even though payments always increase every year, if we look back at the number of Indonesian people who are supposed to fulfil their tax obligations or Indonesian people who are still running away from their responsibility to fulfil their tax obligations, it is still relatively high. This shows that the level of taxpayer compliance is still a major problem for all tax authorities, especially in Indonesia. Research that links taxpayer understanding and tax compliance has been widely conducted, but research that links indirectly between compliance costs to tax compliance is still not widely conducted, especially in Indonesia. This research will be carried out to connect directly between taxpayer understanding and tax compliance and indirectly through tax compliance costs. This type of research is quantitative research. The data used is primary data and the data source was obtained from the One Stop Integrated Services Investment and Manpower Service of Mojokerto City. This research will used Path Analysis. This research is important to conduct to see the role of compliance costs in increasing tax compliance. The results of the study are tax payers understanding has a significant effect on tax compliance and tax payers understanding also has a significant effect on compliance costs. Meanwhile, the indirect influence between tax payers understanding and tax compliance through compliance costs also has a significant effect. But based on the results, the coefficient is still greater for that direct influence. The limitation of this study is that respondents may not be objective in filling out the questionnaire.